Incidencia del desarrollo formativo en la práctica del mini baloncesto en los niños de 9 a 11 años del centro educativo particular bilingüe paraíso de los niños de la ciudad de Machala periodo lectivo 2013-2014 - Guamán Peláez, Nelson Oswaldo (2014)
When we talk about development we refer to basic set of technical skills students individually as players should have to play this sport. These are the four basic elements: passing, dribbling, shooting and defensive moves. On these four aspects are going to build the team play and they will also derive other actions we need to complete the game, such as rebounding, cutting to the basket, the different blocks. These four techniques should be taught from the infant stage, giving them the importance they deserve and without neglect in the folllowing categories. In our, at the present time, the development of learning techniques basketball is very important and of great benefit, as we have seen they have created many schools and sport clubs in our country for practicing and learning this saying sport that helps to improve physical activity, their abilities skills in the practtioner. However it is common knowledge in promothing learning and skills development and life skills students. Many individual and fisical educationl institutions in the province El Oro see there teching nasketball as basic, overall sport very important and applicable to the student´s knowledge. If it is feasible to develop this research as they have Access to empirical information, human, financial, material, time availability and posible profesional advice.